Associations of total and free 25OHD and 1, 25(OH)2D with serum markers of inflammation in older men. Issue 7 (July 2016) - Srikanth, P.; Chun, R.; Hewison, M.; Adams, J.; Bouillon, R.; Vanderschueren, D.; Lane, N.; Cawthon, P.; Dam, T.; Barrett-Connor, E.; Daniels, L.; Shikany, J.; et al.
Abstract Summary Vitamin D is hypothesized to suppress inflammation. We tested total and free vitamin D metabolites and their association with inflammatory markers. Interleukin-6 levels were lower with higher 25-hydroxyvitamin D. 1, 25-dihydroxyvitamin D and free 25OHD associations mirrored those of 25OHD. However, associations for the two metabolites diverged for tumor necrosis factor alpha (TNF-α) soluble receptors. Introduction Vitamin D is hypothesized to suppress inflammation, and circulating 25-hydroxyvitamin D (25OHD) and inflammatory markers are inversely correlated. However, total serum 25OHD may not be the best indicator of biologically active vitamin D. Methods We tested serum total 25OHD, total 1, 25(OH)2 D, vitamin D binding protein (DBP), and estimated free 25OHD and free 1, 25(OH)2 D associations with inflammatory markers serum interleukin-6 (IL-6), TNF-α and their soluble receptors, interleukin-10 (IL-10), and C-reactive protein (CRP) as continuous outcomes and the presence of ≥2 inflammatory markers in the highest quartile as a dichotomous outcome, in a random subcohort of 679 men in the Osteoporotic Fractures in Men (MrOS) study. Results IL-6 was lower in men with higher 25OHD (−0.23 μg/mL per standard deviation (SD) increase in 25OHD, 95 % confidence intervals (CI) −0.07 to −0.38 μg/mL) and with higher 1, 25(OH)2 D (−0.20 μg/mL, 95 % CI −0.0004 to −0.39 μg/mL); free D associations were slightly stronger. 25OHD and DBP, but not 1, 25(OH)2 D, wereindependently associated with IL-6. TNF-α soluble receptors were inversely associated with 1, 25(OH)2 D but positively associated with 25OHD, and each had independent effects. The strongest association with ≥2 inflammatory markers in the highest quartile was for free 1, 25(OH)2 D (odds ratios (OR) 0.70, 95 % CI 0.54 to 0.89 per SD increase in free 1, 25(OH)2 D). Conclusions Associations of 1, 25(OH)2 D and free 25OHD with IL-6 mirrored those of 25OHD, suggesting that 1, 25(OH)2 D and free D do not improve upon 25OHD in population-based IL-6 studies. However, associations for the two metabolites diverged for TNF-α soluble receptor, warranting examination of both metabolites in studies of TNF-α and its antagonists.